2022
DOI: 10.1007/s00442-022-05258-w
|View full text |Cite
|
Sign up to set email alerts
|

Liana functional assembly along the hydrological gradient in Central Amazonia

Abstract: Soil hydrology, nutrient availability and forest disturbance determine the variation of tropical tree species composition locally. However, most habitat ltering is explained by tree species' hydraulic traits along the hydrological gradient. We asked whether these patterns apply to lianas. At the community level, we investigated: (i) whether the hydrological gradient, soil fertility and forest disturbance explain liana species composition; and (ii) whether differences in leaf and stem wood functional traits wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 107 publications
1
7
0
Order By: Relevance
“…For this latter study, the authors modeled climatic data describing a precipitation gradient related to changes in elevation even over small distances in the LTBS and showed the important role of these gradients in palm community differentiation, along with variation in soil water availability. Thus, these environmental variables are interrelated in a complex way and may be key drivers of plant community differentiation, as discussed in other liana studies (Liu et al, 2021(Liu et al, , 2023Manzané-Pinzón et al, 2018;Rocha et al, 2022;Romero-Saltos, 2011). Interestingly, the basal area data produced a contrasting ordination (Figure 5c), suggesting that environmental heterogeneity influences the establishment and biomass accumulation differentially among species.…”
Section: Land Units As Contrasting Habitat Combinations For Lianasmentioning
confidence: 86%
“…For this latter study, the authors modeled climatic data describing a precipitation gradient related to changes in elevation even over small distances in the LTBS and showed the important role of these gradients in palm community differentiation, along with variation in soil water availability. Thus, these environmental variables are interrelated in a complex way and may be key drivers of plant community differentiation, as discussed in other liana studies (Liu et al, 2021(Liu et al, , 2023Manzané-Pinzón et al, 2018;Rocha et al, 2022;Romero-Saltos, 2011). Interestingly, the basal area data produced a contrasting ordination (Figure 5c), suggesting that environmental heterogeneity influences the establishment and biomass accumulation differentially among species.…”
Section: Land Units As Contrasting Habitat Combinations For Lianasmentioning
confidence: 86%
“…The vegetation of the Ducke Reserve was an old-growth perennial rainforest with a high diversity of tree and liana species. The forest has a closed canopy of 30-37 m and emerging trees reaching 45 m (Guillaumet and Kahn, 1982; Ribeiro et al , 1999; Rocha et al , 2022). The topography was heterogeneous, with elevations ranging from 40 to 140 m above sea level (Ribeiro et al , 1999).…”
Section: Methodsmentioning
confidence: 99%
“…When we compare the number of species found in our study area, which attained a larger area than Laurance et al (2001), the number of species was almost double (47.7%) for 2.88 ha in the BDFFP. And for a region 80 km away, at the Ducke Reserve, our study comprises a third (33.1%) of the total lianas species inventoried there (Rocha et al 2022).…”
Section: High Diversity and Site Effectmentioning
confidence: 99%
“…For the BDFFP areas,Laurance et al (2001) found that the abundance of lianas varied with soil edaphic factors, such as fertility, texture, and slope. In the Ducke Reserve, terrain height above nearest drainage (HAND) is a compositional descriptor for two of the most representative liana families: Bignoniaceae and Fabaceae(Schietti et al 2014;Gerolamo et al 2022;Rocha et al 2022). In the studies mentioned above, Bignonia aequinoctialis (Bignoniaceae) was found at shorter distances from the water table.…”
mentioning
confidence: 99%
See 1 more Smart Citation